Designed Molecular Space in Material Science and Catalysis - Shirakawa, Seiji (Springer Nature Singapore : Imprint: Springer, 2018)
This book focuses on molecular space chemistry, which is recognized as an important concept for the design of novel functional materials and catalysts. A wide variety of topics and ideas included in this book are based on that concept. The book showcases recent representative examples of molecular space design to create functional materials and catalysts possessing unique properties. This unique volume will be of great interest to chemists in a wide variety of research fields, including organic, inorganic, biological, polymer, and supramolecular chemistry. Readers will obtain new ideas and directions to create novel functional molecules, and those ideas will lead to innovative views of science. .